2018
DOI: 10.1016/j.ccell.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Co-opt the Neuronal Redox-Sensing Channel TRPA1 to Promote Oxidative-Stress Tolerance

Abstract: Cancer cell survival is dependent on oxidative-stress defenses against reactive oxygen species (ROS) that accumulate during tumorigenesis. Here, we show a non-canonical oxidative-stress defense mechanism through TRPA1, a neuronal redox-sensing Ca-influx channel. In TRPA1-enriched breast and lung cancer spheroids, TRPA1 is critical for survival of inner cells that exhibit ROS accumulation. Moreover, TRPA1 promotes resistance to ROS-producing chemotherapies, and TRPA1 inhibition suppresses xenograft tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(196 citation statements)
references
References 54 publications
12
183
1
Order By: Relevance
“…As a result, the top three differentially expressed genes, namely transient receptor potential cation channel subfamily A member 1 ( TRPA1 ), tetraspanin 17 ( TSPAN17 ) and secretogranin V ( SCG5 ), with the minimum required energy to hybridize with tRF-T11 at their 3’ UTR regions of mRNA, were considered as the potential targets for further experimental validation (Fig 2e). Among these three genes, TRPA1 , a new target recently unveiled by Takahashi et al 24 for cancer therapies, which acts by triggering a noncanonical oxidative stress defense mechanism of tumor suppression, was dramatically downregulated in A2780 cells (by approximately 75%) in a dose-dependent manner by tRF-T11 mimic treatment (Fig 2j, g), while the mRNA levels of the other two targets did not vary significantly (Fig 2f). Furthermore, a marked decrease of over 50% in the protein expression level of TRPA1 was also observed in A2780 cells treated with tRF-T11 mimic (Fig 2h, i), which may act as a translational repressor of the TRPA1 gene by acting like a miRNA in human OVCA cells.…”
Section: Figurementioning
confidence: 89%
“…As a result, the top three differentially expressed genes, namely transient receptor potential cation channel subfamily A member 1 ( TRPA1 ), tetraspanin 17 ( TSPAN17 ) and secretogranin V ( SCG5 ), with the minimum required energy to hybridize with tRF-T11 at their 3’ UTR regions of mRNA, were considered as the potential targets for further experimental validation (Fig 2e). Among these three genes, TRPA1 , a new target recently unveiled by Takahashi et al 24 for cancer therapies, which acts by triggering a noncanonical oxidative stress defense mechanism of tumor suppression, was dramatically downregulated in A2780 cells (by approximately 75%) in a dose-dependent manner by tRF-T11 mimic treatment (Fig 2j, g), while the mRNA levels of the other two targets did not vary significantly (Fig 2f). Furthermore, a marked decrease of over 50% in the protein expression level of TRPA1 was also observed in A2780 cells treated with tRF-T11 mimic (Fig 2h, i), which may act as a translational repressor of the TRPA1 gene by acting like a miRNA in human OVCA cells.…”
Section: Figurementioning
confidence: 89%
“…Antioxidant pathways are necessary for tumorigenesis (DeNicola et al, 2011;Harris et al, 2015) and tumor progression (Deblois et al, 2016;Takahashi et al, 2018). Recent studies have shown that residual tumor cells experience oxidative stress (Havas et al, 2017;Viale et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…4B). Recognizing oxidative-stress heterogeneities in 3D spheroids (21,22,64), we used the genetically-encoded sensor HyPer-2 (65) together with a novel mRFP1-NRF2 reporter (NRF2rep) to colocalize intracellular H2O2 with stabilized NRF2 (see Materials and Methods and fig. S7).…”
Section: Nrf2 and P53 Are Coordinately Stabilized By Sporadic Oxidatimentioning
confidence: 99%